Do Tourism Sectors Contribute to Gross Regional Domestic Product in Sukabumi City? - M. Hanggara Abirawa; Filda Rahmiati; M. Noor Hanafie Zain (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
This paper aims to find out the contribution of tourism sectors to Gross Regional Domestic Product in Sukabumi City. Tourism sectors studied in this paper consist of number of Tourist Attractions, number of Hotels, number of Hotel Guests and number of Restaurants with Regional Income Revenue (PAD) is considered to be the intermediation to Gross Regional Domestic Product (GRDP). Sampling technique used was purposive sample with primary data taken from Department of Tourism and Development Planning Agency in Sukabumi City from 2014 to 2018. The data analyses through quantitative research using statistical analysis and processed by E-Views 8. The result confirms that all tourism sectors except number of Hotel Guests partially does not have a significant influence while as simultaneously have a significant influence to Regional Income Revenue. Further, Regional Income Revenue has a significant influence on Gross Regional Domestic Revenue (GRDP). Based on the result, some actions need to be implemented in order to boost the hotel guests in Sukabumi City.